Preparation and characterization of physicochemical properties of N, N-diethyl-meta-toluamide niosomes - Amanatfard, Arezoo (Int J Pharm Investig, 2015)
INTRODUCTION: The insect repellent compounds are used to protect humans, animals and plants against insect bites. Aromatic amides have insect repellent effects. N,N-diethyl-meta-toluamide (DEET) (C(12) H(17) NO) is one of the best insect repellents has been used for many years. DEET is a colorless, odorless liquid that is approximately insoluble in water and soluble in glycerin, ethanol, and isopropyl alcohol. Due to the solubility problem of DEET, its topical formulations usually have alcoholic bases, but these kind of formulations increase skin permeation and also systemic absorption of DEET, which leads to some toxic effects. The main goal of this study was to prepare the formulation of DEET niosomes in a topical dosage form with suitable stability properties. MATERIALS AND METHODS: Three different methods were used to prepare niosome formulations: Dehydration rehydration vesicle method, direct mixing method, homogenizer method. Sorbitan surfactants, cholesterol, polyoxyethylenecetyl, phosphate buffer (pH 7.4), and charge inductive compounds like cetyltrimethylammonium bromide were used to provide a net negative charge to the final membrane structure. A high-performance liquid chromatography method was then used for the determination of the loaded DEET. RESULTS: A large number of niosomes were multi-layered and have a spherical shape. In comparison, syringe method against direct mixing is more appropriate because of creation MLV and uniform niosomes but the best method is homogenizer method. Drug entrapment was between 14% and 21% in selected formulation. CONCLUSION: According to this study, homogenizing method can be used for formulation of DEET in niosome form in topical formulations.